2015
DOI: 10.1111/ejn.12833
|View full text |Cite
|
Sign up to set email alerts
|

Averaging auditory evoked magnetoencephalographic and electroencephalographic responses: a critical discussion

Abstract: In the analysis of data from magnetoencephalography (MEG) and electroencephalography (EEG), it is common practice to arithmetically average event-related magnetic fields (ERFs) or event-related electric potentials (ERPs) across single trials and subsequently across subjects to obtain the so-called grand mean. Comparisons of grand means, e.g. between conditions, are then often performed by subtraction. These operations, and their statistical evaluation with parametric tests such as ANOVA, tacitly rely on the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 86 publications
(135 reference statements)
1
13
0
Order By: Relevance
“…The comparison of grand mean waveforms across tasks requires homogeneous variance and a normal distribution of the underlying MEG data. We found that this could be achieved by a log-transformation of individual source waveforms, consistent with earlier studies ( König et al, 2015 ; Matysiak et al, 2013 ; Zacharias et al, 2011 ). To obtain the grand mean waveform, the log-transformed source waveforms were arithmetically averaged across subjects and this mean waveform was then back-transformed (by exponentiation) and plotted along a logarithmic axis.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…The comparison of grand mean waveforms across tasks requires homogeneous variance and a normal distribution of the underlying MEG data. We found that this could be achieved by a log-transformation of individual source waveforms, consistent with earlier studies ( König et al, 2015 ; Matysiak et al, 2013 ; Zacharias et al, 2011 ). To obtain the grand mean waveform, the log-transformed source waveforms were arithmetically averaged across subjects and this mean waveform was then back-transformed (by exponentiation) and plotted along a logarithmic axis.…”
Section: Methodssupporting
confidence: 91%
“…They were seeded in the left and right AC, respectively, based on the anatomical MR image of each subject’s brain. To obtain the grand mean source waveforms, individual source waveforms were geometrically averaged across subjects, for reasons given elsewhere ( König et al, 2015 ; Matysiak et al, 2013 ; Zacharias et al, 2011 ). Source strengths were analyzed for correct trials (∼90%) only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal distribution was verified by Shapiro-Wilk test while homogeneity of variance was verified by Levene's test. In turn, Box-Cox transformation was used for variables which did not meet ANOVA assumptions [17, 18]. …”
Section: Methodsmentioning
confidence: 99%
“…However, it is problematic to base theoretical conclusions on the absence of a significant effect. The traditional ANOVA method gives the probability 1 There has been some concern about the use of non-transformed data in hemispheric comparisons (König et al, 2015). However, the data used in this analysis were normally distributed (Shapiro-Wilk tests, p > .175) and applying the recommended ASINH transform did not change the results.…”
Section: Confirmation Of the Null Hypothesismentioning
confidence: 99%